Introduction - Mary Gobbi (Universidad de Deusto, 2021)
When analysing the four papers that comprise this edition of the Journal, there were some quite similar themes, albeit with different perspectives. Essentially, the papers are considering different types of competences, their evolution over time, and the future needs of the work force in specific disciplines. What is fascinating is the emergence of a discourse of competences that is paradoxically extending and becoming more sophisticated on the one hand, yet on the other is confused, locally situated and difficult to define. We find competences being described as global, generic, scientific, technical, and associated with workplace learning. The geography of the papers provides a hierarchy of analysis from an international and global perspective to a sub-regional analysis of five countries (Europe), country based (Chile) and programme specific (The Netherlands).